Design and Performance Analysis of Distributed Equal Angle Spiral Vertical Axis Wind Turbine - Zheng, Li; Wenda, Zhang; Ruihua, Han; Yongsheng, Tian (Recent Patents on Engineering, 2020)
Background: The wind turbine is divided into a horizontal axis and a vertical axis depending on the relative positions of the rotating shaft and the ground. The advantage of the choke wind turbine is that the starting torque is large and the starting performance is good. The disadvantage is that the rotation resistance is large, the rotation speed is low, the asymmetric flow occurs when the wind wheel rotates, the lateral thrust is generated, and the wind energy utilization rate is lowered. How to improve the wind energy utilization rate of the resistance wind turbine is an important issue to be solved by the wind power technology. Objective: The nautilus isometric spiral wind turbines studied in this paper have been introduced and analyzed in detail, preparing for the further flow analysis and layout of wind turbines, improving the wind energy utilization rate of wind turbines, introducing patents of other structures and output characteristics of its generator set. Methods: Combined with the flow field analysis of ANSYS CFX software, the numerical simulation of the new wind turbine was carried out, and the aerodynamic performance of the new vertical axis wind turbine was analyzed. The mathematical model and control model of the generator were established by the maximum power control method, and the accuracy of the simulation results was verified by the measured data. Results: The basic parameters of the new wind turbine tip speed ratio, torque coefficient and wind energy utilization coefficient are analyzed. Changes in wind speed, pressure and eddy viscosity were investigated. Three-dimensional distribution results of wake parameters such as wind speed and pressure are obtained. By simulating the natural wind speed, the speed and output current of the generator during normal operation are obtained. Conclusion: By analyzing the wind performance and power generation characteristics of the new wind turbine, the feasibility of the new wind turbine is determined, which provides reference and reference for the optimal design and development of the wind turbine structure.
Keywords: numerical simulation